燃用掺混小比例生物柴油对船舶柴油机性能的影响 - 张哲1，江国和1，陈优金2，吴刚1 ZHANG Zhe1, JIANG Guohe1, CHEN Youjin2, WU Gang1 (Zhongguo youzhi, 2023)
为探究生物柴油在船舶柴油机上的适用性，基于六缸中速柴油机试验台架，在不同负荷推进特性工况下，对燃用0#柴油、B10生物柴油柴油机的动力性能、经济性能、振动特性和缸内燃烧特性进行对比分析。结果发现：与0#柴油相比，燃用B10生物柴油柴油机的输出功率和耗油量基本不变，耗油率有所升高，但随着负荷的升高有所改善,燃用B10生物柴油使得在25%负荷工况下的柴油机缸盖振动烈度下降，50%、75%、90%、100%负荷工况下的柴油机缸盖振动烈度稍有上升，不同负荷工况下的机体振动烈度均下降；从振动功率谱密度可以看出，两种燃油在不同负荷下低频段的振动响应相似，但高频段处振动响应存在差异；对两种燃油的缸内压力和压力升高率曲线的分析可知，燃用B10生物柴油可以使缸内压力峰值和最大压力升高率升高，燃烧反应速度加快。综上，B10生物柴油在不同负荷工况下动力性能、经济性能、振动特性和缸内燃烧特性方面均表现良好，在船舶柴油机上具有较好的应用前景。 In order to explore the applicability of biodiesel on marine diesel engine, based on a six-cylinder medium-speed diesel engine test bench, under different load propulsion characteristics, the power performance, economic performance, vibration characteristics and combustion characteristics in-cylinder of diesel engine burning 0# diesel and B10 biodiesel were analyzed and compared. The results showed that compared with 0# diesel, the output power and fuel consumption of diesel engine burning B10 biodiesel remained basically unchanged, and the fuel consumption rate increased but improved as the load increased.B10 biodiesel made the vibration intensity of the cylinder head of the diesel engine at 25% load decreased, and the vibration intensity of the cylinder head of the diesel engine at 50%, 75%, 90% and 100% load increased slightly, and the vibration intensity of the engine body decreased under different load conditions. It could be seen from the vibration power spectrum density that the vibration response of the two fuels in the low frequency band under different loads was similar, but there was a difference in the vibration response in the high frequency band.The analysis of the pressure in-cylinder and pressure rise rate curves of the two fuels showed that the combustion of B10 biodiesel could increase the peak pressure and maximum pressure increase rate in the cylinder, which accelerated the combustion reaction speed. In summary, B10 biodiesel performs well in terms of power performance, economic power performance, vibration characteristics and combustion characteristics in-cylinder under different load conditions, and has good application prospect on marine diesel engines.